Increased serum levels and expression of S100A8/A9 complex in infiltrated neutrophils in atherosclerotic plaque of unstable angina. Issue 8 (28th February 2008) - Miyamoto, S; Ueda, M; Ikemoto, M; Naruko, T; Itoh, A; Tamaki, S; Nohara, R; Terasaki, F; Sasayama, S; Fujita, M
Abstract : Background: The S100A8/A9 complex is expressed in a subset of activated neutrophils and macrophages in acute inflammatory lesions associated with various diseases. Objective: To investigate ( a ) whether serum S100A8/A9 levels are increased in patients with unstable angina (UA); and ( b ) whether S100A8/A9 expression is upregulated in coronary atherosclerotic plaques of patients with UA. Design: Serum S100A8/A9 levels in 39 patients with stable angina (SA) and 53 patients with UA were measured. In addition, the presence of the S100A8/A9 complex in directional coronary atherectomy specimens was studied immunohistochemically. Cell types which stain positive for S100A8/A9 were identified by immunodouble staining with neutrophils and macrophages. Results: Mean (SD) serum S100A8/A9 levels were significantly higher in patients with UA than in those with SA (3.25 (3.08) μg/ml vs 0.77 (0.31) μg/ml, p<0.05). In patients with UA, immunodouble staining clearly showed that the S100A8/A9 complex was expressed in infiltrated neutrophils and occasional macrophages. The S100A8/A9-positive area was significantly higher in UA than in SA (mean (SD) 18.3 (14.2)% vs 1.3 (2.4)%, respectively, p<0.001). Conclusions: The S100A8/A9 complex may be involved in the inflammatory process of coronary atherosclerotic plaques in patients with UA.